MicroRNAs in Neuroblastoma: Biomarkers with Therapeutic Potential - Galardi, Angela; Colletti, Marta; Businaro, Pietro; Quintarelli, Concetta; Locatelli, Franco; Di Giannatale, Angela (Current Medicinal Chemistry, 2018)
Background: Neuroblastoma is the most common extracranial solid tumor in infancy. The majority of children have a disseminated disease at diagnosis with bone marrow as the most common site of metastasis. Although several prognostic factors have been defined (i.e. age, stage, histology, recurrent genetic anomalies), the identification of non-invasive biomarkers for disease follow-up and therapy monitoring is indeed still a clinical need. Aberrant regulation of microRNAs (miRNAs) expression has been implicated in several malignancies. Objectives: In this mini-review, we describe the recent findings about miRNAs in neuroblastoma, both in the tumor and circulation, with particular focus on those involved in tumor progression and drug resistance. Furthermore, we will discuss the use of specific miRNAs as potential therapeutic tools in this tumor. Results: Several miRNAs have been identified to be down- or up-regulated in primary tumors and have been associated with MYCN amplification, differentiation, dissemination and chemoresistance. Little evidence is available in the literature about circulating miRNAs which are of particular interest as potential biomarkers for liquid biopsy. Conclusion: Identification of body-fluid markers for non-invasive diagnosis, risk stratification, treatment monitoring and tumor follow-up, is gaining growing interest, especially in the pediatric field. miRNAs are suitable candidates as biomarkers in neuroblastoma but further investigations are needed to expand knowledge regarding their role in this malignancy to design specific approaches of miRNAs-mediated therapies.
Keywords: microRNAs